2002
DOI: 10.1118/1.1445409
|View full text |Cite
|
Sign up to set email alerts
|

Intensity and energy modulated radiotherapy with proton beams: Variables affecting optimal prostate plan

Abstract: Inverse planning for intensity- and energy-modulated radiotherapy (IEMRT) with proton beams involves the selection of (i) the relative importance factors to control the relative importance of the target and sensitive structures, (ii) an appropriate energy resolution to achieve an acceptable depth modulation, (iii) an appropriate beamlet width to modulate the beam laterally, and (iv) a sufficient number of beams and their orientations. In this article we investigate the influence of these variables on the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In the case of prostate cancer Model V, it was observed that a maximum of eleven beam ports was sufficient for IMXT and VHEET, and that the best plan for each modality resulted from the beam arrangement for which the first beam was incident at a gantry angle of approximately 7°. For IMPT the fourfield configuration from {0°, 90°, 180°, 270°} gave the "best" dose distribution for Model V among the set of one to nine-field plans, as reported in chapter 4 (Yeboah et al 2002). TABLE 6.1 summarizes the beam and optimization parameters used for designing the "best" plans for the three modalities under consideration for each prostate cancer model.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…In the case of prostate cancer Model V, it was observed that a maximum of eleven beam ports was sufficient for IMXT and VHEET, and that the best plan for each modality resulted from the beam arrangement for which the first beam was incident at a gantry angle of approximately 7°. For IMPT the fourfield configuration from {0°, 90°, 180°, 270°} gave the "best" dose distribution for Model V among the set of one to nine-field plans, as reported in chapter 4 (Yeboah et al 2002). TABLE 6.1 summarizes the beam and optimization parameters used for designing the "best" plans for the three modalities under consideration for each prostate cancer model.…”
Section: Resultsmentioning
confidence: 77%
“…Model IV is an even more complex target problem that comprises of a butterfly-shaped target overlapping with both sensitive structures where the regions of overlap are taken to be target regions. Finally, Model V is similar to Model IV, however, unlike the latter, the target does not overlap with the rectum or bladder (Yeboah et al 2002). Instead, it is in direct contact with these sensitive structures in the anterior and posterior concavities.…”
Section: Phantoms Consideredmentioning
confidence: 90%
See 1 more Smart Citation
“…6) Unlike proton therapy, all heavyion medical accelerators utilize synchrotron accelerators and a combination of scattering (or passive beam) and scanning (or pencil beam) beam for irradiation. [6][7][8][9][10] However, it is understood that IBA, which has previously operated cyclotron accelerators, is working in tandem with Russia's JINR to install a heavy-ion accelerator based [24][25][26][27] Thus, it is expected, based on the cancer treatment trends in local proton therapy treatment centers, that the proportion of patients opting for heavy-ion medical accelerator treatment would be significant should it be introduced formally. Furthermore, noting that a radiotherapy for cancer in certain organs such as the lung and the liver may potentially result in undesirable side effects on other healthy organs exposed to low doses of radiation, it is possible to predict that the demand for heavy-ion medical accelerator treatment will increase for lung and liver cancer patients, as studies attesting to the ability of heavy-ion accelerators to focus radiation doses on the tumor target and reduce radioactive exposure to the peripheral organs increase in number.…”
Section: Current Usage Trends Of Heavy-ion Medical Acceleratormentioning
confidence: 99%
“…Because of the possibility of giving a homogeneous dose distribution in the target's depth direction, 12,13 one can expect that energy-and intensity-modulated proton therapy ͑EIMPT͒ will further improve target coverage and normal tissue sparing effects. In recent years, the planning and delivery of x rays has improved considerably so that the gap between the conventional proton techniques and x-ray methods has decreased dramatically.…”
Section: Introductionmentioning
confidence: 99%